Numerical simulation on giant reed co-firing performance of circulating fluidized bed in thermal power plant to reduce carbon emission - Jiamiao Liu; Pengbo Zhao; Chenglong Yang; Qingwei Wang; Liujun Chang; Shi'en Liu; Chang'an Wang; Defu Che (Biomass and Bioenergy, 2026)

Coupled simulation of the combustion and hydrodynamics for predicting water-cooled wall temperature of a supercritical boiler during load variations - Chao Wang; Kairui Liu; Zhiyang Ma; Bin Liu; Rongze Gao; Limin Wang; Defu Che (Fuel, 2026)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Elevated hydrostatic pressure promotes organic carbon mineralization in reservoir sediments - Yan Zhang; Shangbin Xiao; Defu Liu; Wenjun Yang; Huiqun Cao; Jia Liu; Chenghao Wang; Li Zhu; Shijian Li; Shiping Lai; Xinghui Xia (Water Research, 2026)

Physics-informed machine learning of hyporheic exchange driven by channel blockage and riverbed morphodynamics - Hang Li; Linlin Li; Defu Liu; Genguang Zhang; Jiahao Zou; Yu Lei; Canyong Li (Journal of Hydrology, 2026)

Emerging soil contamination by hexamethylene and toluene diisocyanates in China: Distribution characteristics and influencing factors - Xiaomu Cao; Xuelong Cao; Yan Liu; Qiuning Hu; Qi Yan; Jiahe Zhuang; Yuqing Liang; Yongming Luo; Defu He (Environmental Pollution, 2026)

Parameterization of ground ice dynamics in permafrost models: Advances, challenges, and future directions - Yifan Wu; Guojie Hu; Lin Zhao; Zhe Sun; Bowen Zhang; Yao Xiao; Defu Zou; Guangyue Liu; Xiaofan Zhu; Tonghua Wu; Xiaodong Wu; Wenxin Zhang; et al. (Earth-Science Reviews, 2026)

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

Enhanced catalytic activity in ion-doped CeO2 via lattice distortion engineering for diketone hydrogenation - Defu Yin; Lu Shen; Xinjun Feng; Shitao Yu; Lu Li; Shiwei Liu; Sai Geng; Yue Liu (Chemical Engineering Journal, 2026)

Evaluation of Rice Yield Attributes, Loach Muscle Quality, and Soil Biochemical Composition Under Rice–Loach Coculture System - Chuanqi Yu; Wenlu Zhu; Wenjun Wang; Wenqiang Xu; Yu Liu; Xingtian Cai; Yanfa Xu; Defu Yang; Zhuqing Yang; Zirui Wang; Qiubai Zhou; Haohua He (Fishes, 2026)
This study aimed to evaluate rice yield attributes, loach Paramisgurnus dabryanus muscle quality, and soil biochemical composition under rice monoculture (RM), rice–loach coculture (RLC), and loach monoculture (LM). This trial was conducted for 90 days, and then rice, fish muscle and soil were obtained for analyses. The results showed that there were no significant differences in rice yield attributes between the rice–loach coculture (RLC) and rice monoculture (RM) groups. However, rice–loach coculture (RLC) improved muscle quality-related parameters, including increased hardness and springiness of loach muscle. Meanwhile, muscle metabolomic analysis showed that all the differentially expressed metabolites (DEMs) in the significantly enriched pathways of lysine degradation and lysine biosynthesis were up-regulated in the rice–loach coculture (RLC) group compared with the loach monoculture (LM) group. Furthermore, the rice–loach coculture (RLC) improved soil physicochemical properties, including an increase in microbial biomass nitrogen (MBN) content and activities of soil N-acquiring enzymes (NAG and LAP). Moreover, soil microbiome analysis showed that the abundance of Candidatus Koribacter versatilis, Acidobacteria bacterium WX27 and Pseudolabrys taiwanensis was significantly increased in the rice monoculture (RM) and rice–loach coculture (RLC) groups compared with the loach monoculture (LM) group. Pairwise Spearman’s correlation analysis of the top 30 soil microbial species and soil physicochemical properties indicated that Terrimonas sp. H1YJ31 showed a highly significant positive correlation with the soil N-acquiring enzymes (N-acetylglucosaminidase, NAG; leucine aminopeptidase, LAP) and a soil C-acquiring enzyme (exo-β-1,4-glucanase C1), whereas Gaiella occulta, Methyloceanibacter marginalis and Anaerohalosphaera lusitana had a highly significant negative correlation with S-NAG, S-LAP and S-C1. In short, the improved fish muscle quality and soil biochemical composition were ascribed to the increased hardness and springiness of loach muscle and the abundance of soil Terrimonas sp. H1YJ31.

Deciphering the impact of soil nutrients on diversity and functional genes of bacteria within the upper 3 m soil under different land cover types - Xiaoying Fan; Xiaodong Wu; Qian Luo; Tonghua Wu; Guimin Liu; Defu Zou; Guojie Hu; Yadong Liu; Xianhua Wei; Xuchun Yan; Yongxiang Liu; Sizhong Yang; et al. (CATENA, 2026)

Multi-component dissolved gas dynamics as early warning indicators for algal bloom development in the three gorges reservoir - Chenyu Wei; Dian Li; Hao Li; Yanan Huang; Xiaojuan Guo; Hao Zhang; Danli Deng; Defu Liu; Zhengjian Yang (Water Research, 2026)

In-situ radical polymerization for solid polymer electrolytes in lithium-ion batteries: a comprehensive review - Yong Luo; Churu Zhang; Ya Liao; Zhitian Ding; Defu Li; Lufa Zhu; Hao Luo; Beiyuan Liu; Jiali Guo; Xiaoli Peng; Shipai Song; Yong Xiang; et al. (Chemical Engineering Journal, 2026)

LSSCM-MobileTeaNet: A UAV-based lightweight spatial–spectral convolution model for large-scale estimation of chlorophyll and nitrogen content in tea plantations - Guoquan Pei; Defu Liu; Hongyuan Shi; Zhengzhao Pi; Xueying Qian; Bing Zhou; Baijuan Wang; Wendou Wu (Computers and Electronics in Agriculture, 2026)

Full-scale experimental study of flame behavior and thermal distribution in utility tunnel fires - Xiaojiang Liu; Zhao-Dong Xu; Jun Dai; Jiayu Che; Zhong-Wei Hu; Defu Che (Tunnelling and Underground Space Technology, 2026)

Nitrogen removal dynamics in a eutrophic-tributary of China's Three Gorges Reservoir during water impoundment period: Insights from denitrification rates and dissolved N2 measurements - Yanan Huang; Yanxing Han; Xiaojuan Guo; Zhengjian Yang; Daobin Ji; Shangbin Xiao; Defu Liu (Journal of Environmental Sciences, 2026)

Gp8 mediates adsorption of bacteriophage vB_VpP_jzsmvpa to the host Vibrio parahaemolyticus - Shuxuan Li; Xiaoni Wang; Jing Li; Ming Zhang; Ke Liu; Xuepeng Li; Jianrong Li; Chunyan Li; Defu Zhang (Antonie van Leeuwenhoek, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Benchmarking and lightweight correction of daily near-surface air temperature products over the Qinghai-Tibetan Plateau - Nan Zhou; Yao Xiao; Lin Zhao; Guojie Hu; Lingxiao Wang; Chong Wang; Ren Li; Guangyue Liu; Defu Zou; Xiangfei Li (Atmospheric Research, 2026)

Acid-triggered degradation of a silicon-based nanopesticide activates SA-dependent conifer defense against Dioryctria sylvestrella - Zheng Wang; Antong Ma; Jiaxing Fang; Xiaoqi Xu; Wei Gan; Jiayue Liu; Fu Liu; Sufang Zhang; Defu Chi; Dafeng Chen; Yapei Wang; Xiangbo Kong (Pesticide Biochemistry and Physiology, 2026)

High-resolution (30 m) mapping of permafrost distribution in the Genhe River Basin, Greater Khingan Mountains, Northeast China - Xueling Jiao; Lin Zhao; Defu Zou; Lingxiao Wang; Chong Wang; Yuanwei Wang; Guojie Hu; Erji Du; Yao Xiao; Guangyue Liu; Shibo Liu; Yuxin Zhang; et al. (Journal of Mountain Science, 2026)

Kinetic insights into the effects of coal quality and operating parameters on the NO and N2O formation behaviors in fluidized bed coal/ammonia co-combustion - Liangxu Dai; Ke Liu; Chang’an Wang; Yujie Hou; Tianlin Yuan; Zixiu Jia; Qiang Lyu; Defu Che (Fuel, 2026)

Ctab-mediated core-shell Pd-based nanocatalysts: pore engineering and N-doping synergy for efficient phenol hydrogenation to cyclohexanone - Lu Shen; Defu Yin; Zewei Hu; Dongyu Liu; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Fuel, 2026)

Evaluation of stability and cooling engineering effectiveness of the Qinghai-Tibet transportation routes: A first comprehensive assessment using space geodetic observations - Lingxiao Wang; Lin Zhao; Shibo Liu; Huayun Zhou; Guojie Hu; Defu Zou; Erji Du; Guangyue Liu; Yao Xiao; Yueli Chen; Jianting Zhao; Wei Chen; et al. (Engineering Geology, 2026)

NO heterogeneous reduction during oxy-fuel combustion of semi-coke: The role of high-temperature rapid gasification - Pengqian Wang; Chenxi Zhang; Xingpeng Li; Jiaojiao Zhang; Yi Liu; Yongbo Du; Chang’an Wang; Defu Che; Bo Bai (Fuel, 2026)

Retraction notice to “Targeted delivery of honokiol by zein/hyaluronic acid core-shell nanoparticles to suppress breast cancer growth and metastasis” [Carbohydr. Polym. 240 (2020) 116325 - Qi Zhang; Jing Wang; Dan Liu; Wenquan Zhu; Shuang Guan; Li Fan; Defu Cai (Carbohydrate Polymers, 2026)

Spatial distribution of vegetation type in the Genhe River Basin based on multi-source data - Zhinan Zhou; Chong Wang; Lin Zhao; Defu Zou; Guangyue Liu; Shibo Liu; Lingxiao Wang; Guojie Hu; Zanpin Xing; Erji Du; Yao Xiao; Xueling Jiao (International Journal of Remote Sensing, 2025)

In situ acoustic quantification of methane ebullition in Xiangxi Bay, Three Gorges Reservoir - Chenyu Wei; Zhengjian Yang; Dian Li; Yanan Huang; Xiaojuan Guo; Defu Liu (Environmental Monitoring and Assessment, 2025)

Control of backfill ratio in a short-wall green-intelligent mining working face to prevent pollution from coal-based solid waste: experimental and design studies on the relationship between two-dimensional images and volume of gangue - Yun Zhang; Yixuan Yang; Xingping Lai; Shenggen Cao; Yongzi Liu; Mingbo Chi; Defu Zhu; Baiyi Li; Di Wang; Jifeng Li (Journal of Cleaner Production, 2025)

Lattice Boltzmann simulation on adsorption of sulfuric acid vapor by ash particles - Jiyun Ren; Chongjun Jiang; Fangfang Hu; Hui Wang; Yunhao Shao; Xinyu Liu; Zhang Wu; Feng Pan; Qidong Yang; Lei Deng; Defu Che (Fuel, 2025)

Redox diverse Co+2/Co+3 species embedded 3D nanoconfined silica walls as an efficient catalyst for fast oxidative desulfurization of fuel oil - Mateen Ahmad; Usman Ali; Afaq Nazir; Xiaoqi Liu; Haoran Sun; Haonan Zhang; Defu Yin; Alieu Kamara; Hanbao Li; Zhen Liu; Zifeng Yan (Fuel, 2025)

Corrigendum to “Hyaluronic acid-modified liposomal honokiol nanocarrier: Enhance anti-metastasis and antitumor efficacy against breast cancer” [Carbohydr. Polym. 235 (2020) 115981] - Jing Wang; Dan Liu; Shuang Guan; Wenquan Zhu; Li Fan; Qi Zhang; Defu Cai (Carbohydrate Polymers, 2025)

Preferential Flow in Common Low Impact Development Technologies: A Review - Ruifen Liu; Junqi Zhou; Ting Fong May Chui; Defu Liu; Ying Liu (Water Resources Management, 2025)
Preferential flow, a common phenomenon in natural soils, has received limited attention in low impact development technologies (LIDs), despite its potential impact on stormwater performance. This paper provides a comprehensive review of the effects, detection and modelling of preferential flow in three common LID systems: green roofs, bioretention, and pervious pavements. While preferential flow negatively affects the retention and detention performance of green roofs, it is considered beneficial for mitigating clogging in bioretention systems. Coarse-grained LID media, such as green roof substrates, bioretention media and pavement aggregates, are particularly susceptible to preferential flow, with plant interactions adding complexity to its formation. Several attempts have been made to characterize preferential flow in LID media through detection techniques based on water movement, breakthrough curves, and dye tracing. As an advanced technique, X-ray scanning has also been introduced for the noninvasive identification of preferential flow. The dual-porosity model is a simple and effective tool for accounting for preferential flow in LID; however, determining the required parameters for multilayered systems, such as pervious pavements, remains a significant challenge. Future research should focus on monitoring preferential flow in field-scale LIDs, investigating the factors influencing preferential flow initiation, and optimizing the stormwater performance of LIDs in the presence of preferential flow.

Quantifying the soil water content of the permafrost active layer using InSAR deformation - Erji Du; Lingxiao Wang; Lin Zhao; Huayun Zhou; Shibo Liu; Defu Zou; Guangyue Liu; Yao Xiao; Guojie Hu; Zhibin Li; Junqiang Gao; Chong Wang; et al. (Journal of Hydrology, 2025)

Simulation study on mineral transformation behaviors and ash fusion characteristics during high-alkali coal combustion under deep peaking conditions - Jiamiao Liu; Guowei Ma; Yongbo Du; Chang’an Wang; Yonggang Zhao; Wanzhu Wu; Longping Shi; Lin Zhao; Defu Che (Fuel, 2025)

A probabilistic formula for sediment incipient motion on combined sloping beds by considering the hiding-exposure effect - Linlin Li; Hang Li; Genguang Zhang; Yao Xiao; Defu Liu; Yu Lei; Maohua Le (Hydrological Sciences Journal, 2025)

Soil fauna Protaetia brevitarsis mediated polyethylene microplastic biodegradation - Jie Jiang; Yan Liu; Qiuning Hu; Qi Yan; Jiahe Zhuang; Xuelong Cao; Wei-Min Wu; Defu He (Science of The Total Environment, 2025)

Study on the mechanism of multiple sodium salts co-loading on ash fusibility and mineral evolution behaviors - Hongli Liang; Jinhao Yi; Yang Yang; Lei Zhang; Tao Ma; Weibin Chen; Hu Liu; Defu Che (Fuel, 2025)

Earthworms multifacetedly drive size- and type-dependent microplastic transport in soils - Xiaoting Zhang; Yan Liu; Defu He (Environmental Pollution, 2025)

Threshold-governed insulating and cooling effects of snow cover on alpine permafrost: evidence from the Qinghai–Tibet Plateau - Yao Xiao; Guojie Hu; Ren Li; Tonghua Wu; Xiaodong Wu; Guangyue Liu; Defu Zou; Zanpin Xing; Jimin Yao; Chong Wang; Lin Zhao (Agricultural and Forest Meteorology, 2025)

Nitrogen and phosphorus release from a dominant plant in the water-level fluctuation zone of the Three Gorges Reservoir - Ying Liu; Ziyan Lu; Genghua Wu; Defu Liu; Henglin Xiao; Hong Yang; Heyun Wang; Jinhong Feng (Aquatic Sciences, 2025)

Improving the moving-grid permafrost model to reveal ground deformation and hydrothermal effects caused by permafrost evolution in the source region of the Yangtze river on the Qinghai-Tibet plateau - Zhe Sun; Lin Zhao; Guojie Hu; Shibo Liu; Yongping Qiao; Erji Du; Defu Zou; Guangyue Liu; Lingxiao Wang; Jianting Zhao (Environmental Modelling & Software, 2025)

A coupled model of surface water-groundwater interaction with the effect of riverbed deformation in the alluvial channel - Linlin Li; Hang Li; Genguang Zhang; Defu Liu; Yao Xiao; Ying Liu; Jiahao Zou (CATENA, 2025)

Land cover types and depth regulate carbon and nitrogen cycle functional genes in permafrost regions on the Qinghai-Tibet Plateau - Xiaoying Fan; Xiaodong Wu; Dejincuo Ma; Tonghua Wu; Guimin Liu; Haiyan Xu; Defu Zou; Guojie Hu; Yadong Liu; Xianhua Wei; Xuchun Yan; Yongxiang Liu; et al. (Plant and Soil, 2025)

Promising eco-friendly agents targeting Pseudomonas fluorescens biofilms - Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li; Lu Wang; Xue Bai (Food Bioscience, 2025)

Corrigendum to “Inhibition of growth and metastasis of breast cancer by targeted delivery of 17-hydroxy-jolkinolide B via hyaluronic acid-coated liposomes” [Carbohydr. Polym. 257 (2021) 117572] - Dan Liu; Qi Zhang; Jing Wang; Shuang Guan; Defu Cai; Jicheng Liu (Carbohydrate Polymers, 2025)

The surface features and internal structure of an integrated open system pingo in the source area of the Yangtze River on the Qinghai-Tibet Plateau - Guangyue Liu; Yao Xiao; Guojie Hu; Tonghua Wu; Xiaodong Wu; Lingxiao Wang; Changwei Xie; Defu Zou; Erji Du; Yonghua Zhao; Yingying Lu; Lin Zhao (CATENA, 2025)

Ground surface deformation in permafrost region on the Qinghai-Tibet Plateau: A review - Shibo Liu; Lin Zhao; Lingxiao Wang; Lin Liu; Defu Zou; Guojie Hu; Zhe Sun; Yuxin Zhang; Wei Chen; Xueying Wang; Meng Wang; Huayun Zhou; et al. (Earth-Science Reviews, 2025)

Preparation and application of bioadhesive hydrogel powder loaded with quorum sensing inhibitor isomaltitol for salmon preservation - Ke Liu; Ming Zhang; Wutong Bai; Wenjing Yang; Xinran Lv; Xue Bai; Xuepeng Li; Defu Zhang; Jianrong Li (Food and Bioproducts Processing, 2025)

Optimization of enzymatic hydrolysis of collagen and screening and application of hypolipidemic peptide - Yancheng Bi; Ming Zhang; Ke Liu; Xinran Lv; Xuepeng Li; Xue Gao; Fangchao Cui; Defu Zhang; Jianrong Li (Food Bioscience, 2025)

Modeling of sediment exchange process and channel evolution in the downstream reach below the Three Gorges Dam - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Defu Liu; Hang Li; Yu Lei (CATENA, 2025)

Targeted phytogenic compounds against Vibrio parahaemolyticus biofilms - Xue Bai; Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li (Critical Reviews in Food Science and Nutrition, 2025)

Retrieval of 1 km surface soil moisture from Sentinel-1 over bare soil and grassland on the Qinghai-Tibetan Plateau - Zanpin Xing; Lin Zhao; Lei Fan; Gabrielle De Lannoy; Xiaojing Bai; Xiangzhuo Liu; Jian Peng; Frédéric Frappart; Kun Yang; Xin Li; Zhilan Zhou; Xiaojun Li; et al. (Remote Sensing of Environment, 2025)

PdH as the hydrogen transporter for phenol hydrogenation reaction - Defu Yin; Zewei Hu; Yunxi Hou; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Chemical Engineering Journal, 2025)

Threshold of sediment incipient motion on a three-dimensional riverbed by considering the hiding-exposure effect with experimental investigations - Linlin Li; Yao Xiao; Genguang Zhang; Yu Lei; Hang Li; Defu Liu (Acta Geophysica, 2024)

Process and mechanism analysis of typical permafrost area surface deformation at two sites along the Qinghai-Tibet highway based on long-term leveling observation - Shibo Liu; Lin Zhao; Lingxiao Wang; Defu Zou; Guojie Hu; Zhe Sun; Huayun Zhou; Yongping Qiao (Science of The Total Environment, 2024)

Cascaded reservoirs promote phosphorus bioavailability of surface sediments in the Upper Mekong River - Zhengjian Yang; QiFeng Min; Xiaojuan Guo; Congfeng Wang; Bi'’e Yan; Xiaoling Li; Defu Liu; Jun Ma; Andreas Lorke (Science of The Total Environment, 2024)

Evolution of self-assembled amphiphilic colloidal particles in strong-flavor Chinese baijiu - Xinyue Jiang; Defu Liu; Shengzhi Yang; Xiang Cheng; Yuqun Xie (Food Chemistry, 2024)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

Progress in phosphorylation of natural products - Xiaoran Mao; Jiaqi Chen; Yingrui Yao; Defu Liu; Haiying Wang; Yuzhou Chen (Molecular Biology Reports, 2024)

Enhancing biofilm formation with powder carriers for efficient nitrogen and phosphorus removal - Yi Yang; Yuting Zhu; Defu Gan; Xiang Cai; Xiaodi Li; Xinchao Liu; Siqing Xia (Science of The Total Environment, 2024)

Efficient and stable Pd catalyst confined in microporous carbon shells for phenol hydrogenation - Zewei Hu; Defu Yin; Hanli Zheng; Yunxi Hou; Lu Shen; Dongyu Liu; Wenman Liu; Ruixin Pang; Yue Liu (Chemical Engineering Journal, 2024)

Experimental investigation on product and temperature distribution in a continuous flow packed-bed reactor for dodecahydro-N-ethylcarbazole dehydrogenation - Jingwen Xue; Pengzhao Li; Pengfei Yu; Jinhao Yi; Tao Ma; Hu Liu; Defu Che (Chemical Engineering Journal, 2024)

Self-supporting electrodes for high-performance flexible solid-state supercapacitors: Recent advances and perspectives - Yanxin Liao; Defu Tang; Shile Liu; Tianrui Liu; Lingyun Chen; Qichun Zhang (Chemical Engineering Journal, 2024)

Methane dynamics altered by reservoir operations in a typical tributary of the Three Gorges Reservoir - Jia Liu; Fei Xue; Xiaojuan Guo; Zhengjian Yang; Manchun Kang; Min Chen; Daobin Ji; Defu Liu; Shangbin Xiao; Chenghao Wang (Water Research, 2024)

Effects of drought and moisture stress on the growth and ecophysiological traits of Schima superba seedlings - Kashif Hussain; Defu Wang; Asif Riaz; Emily Patience Bakpa; Guilin Wu; Suping Liu; Yanxia Nie; Hui Liu (Photosynthesis Research, 2024)

Effects of dietary Allium mongolicum Regel powder supplementation on the growth performance, meat quality, antioxidant capacity and muscle fibre characteristics of fattening Angus calves under heat stress conditions - Wangjing Liu; Huixia Gao; Jianjian He; Aihuan Yu; Chenxu Sun; Yaodi Xie; Haibo Yao; He Wang; Yueyan Duan; Jinsheng Hu; Defu Tang; Tao Ran; et al. (Food Chemistry, 2024)

Soil-dwelling grub larvae of Protaetia brevitarsis biodegrade polystyrene: Responses of gut microbiome and host metabolism - Jie Jiang; Haowen Xu; Xiaomu Cao; Yuqing Liang; Aoyun Mo; Xuelong Cao; Yan Liu; Mark Eric Benbow; Craig S. Criddle; Wei-Min Wu; Defu He (Science of The Total Environment, 2024)

Polymer chain extenders induce significant toxicity through DAF-16 and SKN-1 pathways in Caenorhabditis elegans: A comparative analysis - Aoyun Mo; Yuqing Liang; Xiaomu Cao; Jie Jiang; Yan Liu; Xuelong Cao; Yuping Qiu; Defu He (Journal of Hazardous Materials, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

Efficient synthesis of furfural over mZSM-5@SO42-/mSiO2 core–shell catalyst by targeted regulating B/L acids - Renjie Ji; Defu Yin; Yao Chen; Like Ma; Fanglin Lv; Yuhao Zhang; Zhen Jia; Jingyun Zhang; Mingya Liu; Shitao Yu; Yue Liu (Fuel, 2024)

Influence of the in-stream structures and parameters variation on transient storage - Junxiong Luo; Ying Liu; Defu Liu; Jinghong Feng; Yongsheng Guo; Xunchuan Song; Hanyue Zhang (Ecological Engineering, 2024)

Highly stereoselective hydrogenation of α‑pinene over Ir nanoparticles confined in SiO2 shells - Defu Yin; Zewei Hu; Mingya Liu; Jingyun Zhang; Hanli Zheng; Yunxi Hou; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Chemical Engineering Journal, 2024)

Polystyrene nanospheres-induced hepatotoxicity in swamp eel (Monopterus albus): From biochemical, pathological and transcriptomic perspectives - Weiwei Lv; Haotian Gu; Defu He; Zhiquan Liu; Chunxia Yao; Weiwei Huang; Quan Yuan; Wenzong Zhou (Science of The Total Environment, 2023)

Variable drivers of surface turbulence under condition of stratified density currents in a tributary bay of Three Gorges Reservoir - Lianghong Long; Hui Xu; Meng Yan; Xia Yang; Xingxing Zhao; Daobin Ji; Yujie Cui; Zhongyong Yang; Defu Liu; Zhengjian Yang (Journal of Hydrology, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

The transcription factor CEBP homolog of Penaeus vannamei contributes to WSSV replication - Chuanqi Wang; Huimin Zhang; Jinghua Zhu; Haiping Liu; Yiqing Yang; Bingbing Sun; Tingchu Wu; Yueling Zhang; Defu Yao (Fish & Shellfish Immunology, 2023)

Activity enhancement of core–shell Pd@mCeO2 catalysts for phenol hydrogenation to cyclohexanone by tuning metal-support interactions - Defu Yin; Renjie Ji; Jingyun Zhang; Shitao Yu; Lu Li; Shiwei Liu; Long Jiang; Ying Liu; Zhanqian Song; Yue Liu (Fuel, 2023)

Highly efficient conversion of phenol to cyclohexanone on Pd-based catalysts by cobalt doping - Defu Yin; Renjie Ji; Fanglin Lv; Long Jiang; Jingyun Zhang; Mingya Liu; Zhen Jia; Shitao Yu; Ruiyang Zhao; Yue Liu (Fuel, 2023)

Hydrogenation of N-ethylcarbazole with Hydrogen-Methane mixtures for hydrogen storage - Hu Liu; Jingwen Xue; Pengfei Yu; Yankang Zhang; Jinhua Wang; Defu Che (Fuel, 2023)

DRAXIN as a Novel Diagnostic Marker to Predict the Poor Prognosis of Glioma Patients - Yulong Jia; Zhendong Liu; Xingbo Cheng; Runze Liu; Pengxu Li; Defu Kong; Wenjia Liang; Binfeng Liu; Hongbo Wang; Xingyao Bu; Yanzheng Gao (Journal of Molecular Neuroscience, 2022)
An increasing number of evidences have shown that the carcinogenic effect of DRAXIN plays an important role in the malignant process of tumors, but the mechanism of its involvement in glioma has not yet been revealed. The main aim of this study is to explore the relationship between DRAXIN and the prognosis and pathogenesis of glioma through a large quality of data analysis. Firstly, thousands of tissue samples with clinical information were collected based on various public databases. Then, a series of bioinformatics analyses were performed to mine data from information of glioma samples extracted from several reputable databases to reveal the key role of DRAXIN in glioma development and progression, with the confirmation of basic experiments. Our results showed that high expression of the oncogene DRAXIN in tumor tissue and cells could be used as an independent risk factor for poor prognosis in glioma patients and was strongly associated with clinical risk features. The reverse transcription-quantitative PCR technique was then utilized to validate the DRAXIN expression results we obtained. In addition, co-expression analysis identified, respectively, top 10 genes that were closely associated with DRAXIN positively or negatively. Finally, in vitro experiments demonstrated that knockdown of DRAXIN significantly inhibited proliferation and invasion of glioma cell. To sum up, this is the first report of DRAXIN being highly expressed in gliomas and leading to poor prognosis of glioma patients. DRAXIN may not only benefit to explore the pathogenesis of gliomas, but also serve as a novel biological target for the treatment of glioma.

Comparison of the Homology Between Muskrat Scented Gland and Mouse Preputial Gland - Xiangyu Han; Yuanlin Jiang; Nuannuan Feng; Pengcheng Yang; Meishan Zhang; Weijiang Jin; Tianxiang Zhang; Zhixin Huang; Haoxi Zhao; Kexin Zhang; Shuqiang Liu; Defu Hu (Journal of Mammalian Evolution, 2022)

Adaptability of organic matter and solid content to Fe2+/persulfate and skeleton builder conditioner for waste activated sludge dewatering - Xiaoran Li; Yafei Shi; Xi Zhou; Lu Wang; Huiqin Zhang; Kewu Pi; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2022)

Enhanced dewater efficiency for river sediment by top-to-bottom water transmitting channels with different materials - Zhuo Shi; Kewu Pi; Xuanming Huang; Yafei Shi; Ziwen Chen; Ruyu Tang; Zehui Hu; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2020)

The influence of extensive green roofs on rainwater runoff quality: a field-scale study in southwest China - Ruifen Liu; Richard L. Stanford; Yun Deng; Defu Liu; Ying Liu; Shaw L. Yu (Environmental Science and Pollution Research, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Comparative study of carboxylic acid adsorption on calcite: l-malic acid, d-malic acid and succinic acid - Zhenxuan Li; Jiangtian Xiao; Lidong Huang; Defu Xu; Dagang Liu; Xiaowen Sun; Luji Yu; Hongsheng Wu (Carbonates and Evaporites, 2019)

In-depth proteomic profiling of the Singapore grouper iridovirus virion - Defu Yao; Yingfu Liu; Xiuli Chen; Teck Kwang Lim; Lili Wang; Jude Juventus Aweya; Yueling Zhang; Qingsong Lin (Archives of Virology, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Deep sequencing analysis of a strain of pecan mosaic-associated virus infecting Atractylodes macrocephala Koidz - Yanbing Niu; Xiaojing Pang; Defu Wang; Shang Guo; Yong Liu (Journal of Plant Pathology, 2018)

Molecular detection of watermelon mosaic virus associated with a serious mosaic disease on Cucurbita pepo L. in Shanxi, China - Yanbing Niu; Xiaojing Pang; Yuanyuan Cheng; Defu Wang; Shang Guo; Yong Liu (VirusDisease, 2017)

Development of matrix solid-phase dispersion coupled with high-performance liquid chromatography for determination of jolkinolide A and jolkinolide B in Euphorbia fischeriana Steud. - Defu Cai; Weiyu Zhai; Qi Zhang; Jianhua Liu; Yu Sun; Lei Liu; Jicheng Liu (Natural Product Research, 2017)

Isolation, Immobilization, and Degradation Performance of the 17β-Estradiol-Degrading Bacterium Rhodococcus sp. JX-2 - Jingxian Liu; Juan Liu; Defu Xu; Wanting Ling; Shunyao Li; Mindong Chen (Water, Air, & Soil Pollution, 2016)

Behavioral and physiological responses of forest musk deer (Moschus berezovskii) to experimental fawn manipulation - Wenxia Wang; Lan He; Shuqiang Liu; Torsten Wronski; Defu Hu (acta ethologica, 2016)

The change of organic matter in sewage sludge composting and its influence on the adsorption of pentachlorophenol (PCP) - Lou Liping; Liu Defu; Chen Huanyu; Chen Fang; He Yunfeng; Tian Guangming (Environmental Science and Pollution Research, 2015)

Acteoside reduces testosterone by inhibiting cAMP, p450scc, and StAR in rat Leydig cells - Shuqiang Liu; Junwen Zhang; Weixuan Li; Tianxiang Zhang; Defu Hu (Molecular & Cellular Toxicology, 2015)

Juvenile silver carp Hypophthalmichthys molitrix swim faster in closed surface flow than open surface flow - Xiaotao Shi; Qiuwen Chen; Defu Liu; Yingping Huang; Ping Zhuang; Bo Lu (Environmental Biology of Fishes, 2014)

Nutrient spatial pattern of the upstream, mainstream and tributaries of the Three Gorges Reservoir in China - YuLing Huang; Ping Zhang; DeFu Liu; ZhengJian Yang; DaoBin Ji (Environmental Monitoring and Assessment, 2014)

Evaluation of fecal DNA preservation and extraction methods in Przewalski’s horse - Gang Liu; Sen Zang; Linhai Li; Xiaolong Hu; Shasha Zhao; Kai Li; Defu Hu (Conservation Genetics Resources, 2014)

Cloning and characterization of the NPCEDRG gene promoter - Defu Hou; Yongjun Guan; Jianping Liu; Zhefeng Xiao; Yongmei Ouyang; Yanhui Yu; Zhuchu Chen (Molecular and Cellular Biochemistry, 2011)

Study on the breakwater caisson as oscillating water column facility - Yan Huang; Hongda Shi; Defu Liu; Zhen Liu (Journal of Ocean University of China, 2010)

Typhoon disaster in China: prediction, prevention, and mitigation - Defu Liu; Liang Pang; Botao Xie (Natural Hazards, 2009)

Assessing Genetic Diversity of Chinese Cultivated Barley by STS Markers - Xiwen Chen; Shaoying Guo; Defu Chen; Pin Liu; Xiangdong Jia; Lijun Sun (Genetic Resources and Crop Evolution, 2006)

A preliminary study of trace elements in plasma protein by gel chromatography combined with SXRF - Nianqing Liu; Plngsheng Liu; Kongjiang Wamg; Defu Chen; Jinyuan Zhao; Qing Xu (Biological Trace Element Research, 1999)